2015
DOI: 10.1007/s10008-015-2976-7
|View full text |Cite
|
Sign up to set email alerts
|

Electrospun porous carbon nanofibers as lithium ion battery anodes

Abstract: Porous carbon nanofibers were fabricated by electrospinning in a precursor solution containing polyacrylonitrile (PAN), polymethyl methacrylate (PMMA), and N,Ndimethylformamide. During thermal treatment, PMMA decomposition caused nanofibers to transform from a solid to a porous structure. Removal of PMMA also decreased the fiber diameter and increased the pore volume of the carbon nanofibers, resulting in a substantial increase in specific surface area. We used these web-type fiber films directly without a bin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
1
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(35 citation statements)
references
References 48 publications
2
31
1
1
Order By: Relevance
“…6, the adsorption occurring was at relative pressure smaller than 0.2 because of the micropores, and mesopores lead to the adsorption occurring at relative pressure larger than 0.8. 54 The results showed that the exists macropore and hierarchical pores in rGO/CSn. Table 1 showed the specic surface area and the porosity parameters.…”
Section: Bet Analysis Of Rgo/csnmentioning
confidence: 95%
“…6, the adsorption occurring was at relative pressure smaller than 0.2 because of the micropores, and mesopores lead to the adsorption occurring at relative pressure larger than 0.8. 54 The results showed that the exists macropore and hierarchical pores in rGO/CSn. Table 1 showed the specic surface area and the porosity parameters.…”
Section: Bet Analysis Of Rgo/csnmentioning
confidence: 95%
“…The layered structure of graphite [6] U poslednje vreme se ulažu veliki napori sa ciljem da se povećaju radne performanse i kapacitet anodnog materijala u Li-jonskoj bateriji. Među novim anodnim materijalima su: ugljenične nanocevi [32], ugljenična nanovlakna [33], grafen [34], porozni ugljenik [35], silicijum-oksid [36], silikon [37], germanijum [38], kalaj [39], oksidi prelaznih metala [40], metalni sulfidi [41], fosfidi [42], nitridi [43] itd. Radne performanse nekih od najčešće korišćenih anodnih materijala su date u tabeli 2, dok je na slici 5 dato poređenje elektrohemijskih osobina katodnih i anodnih materijala.…”
Section: Anodaunclassified
“…Particularly, 1D carbon nanofibers have been considered as one type of carbon due to their 1D conductive nanostructure conducive to by facilitating electrolyte transportation and electron transfer . Typically, electrospinning technology is a reliable and versatile method in fabricating 1D nanostructured polymer, which can be easily converted into conductive carbon nanofibers by the further pyrolysis process . Additionally, the heteroatoms (e.g., phosphorous, sulfur, and nitrogen) doped in carbon architecture is also an effective way to tune their physicochemical properties by expanding the graphite‐like interlayer distance, introducing ample defects and porosities, and enhancing electric conductivity, which are of benefit for improving the reversible capacity and rate capability …”
Section: Introductionmentioning
confidence: 99%